Effects of computer assisted pedagogy, time-management and students’ attitude on achievement in junior secondary school civic education in Oyo State (2017)
Effects of computer assisted pedagogy, time management and students’ attitude to achievement in junior secondary school civic education in Oyo State were investigated. The study adopted pretest, post-test and control group quasi-experimental design using a 3x2x2 factorial matrix. Multistage sampling procedure was adopted to select two local government areas, eight junior secondary schools, 385 JSS II students and eight civic education teachers for the study. Seven null hypotheses and four validated instruments were used to collect data for the study. These are: Civic Education Achievement Test (r = 0.83); Civic Education Attitudinal Scale (a — 0.89); Time Management Observation Scales for Teachers (r = 0.75) and Operational Manual of Instruction on Computer Assisted Pedagogy (r = 0.73). Data were analysed using analysis of covariance (ANCOVA) and multiple classification analysis (MCA). Major findings of this research work show that there is a significant effect of treatment on students' achievement; a significant effect of students' attitude on students’ achievement and a significant interaction effect of treatment and student attitude towards students’ achievement. There is no significant main effect of teachers’ time management on students’ achievement at F(1.327) = 46.793 P < 0.05 and no significant interaction effect of teachers’ time management and students’ attitude towards students’ achievement at F(,372)0.301; P > 0.05. Thus, it is recommended that teachers as implementers of curriculum, must diversify in the use of instructional strategies, upgrade continually in knowledge, skills and abilities, inculcate the use of ICT in the classroom setting and learn to be effective time managers in classroom management and dissemination of instructions.